Taiping - Donghak : Ideologies for The Popular Movements in the Last Dynasties of China and Korea - เจนสิริผล ณัฐวดี; ดาบเพชร ศิริพร (Thai Journal of East Asian Studies, 2021)
This research article attempts to analyse and study the contexts and ideologies that lead to the Taiping popular movement and the Donghak popular movement. The results of the study revealed that the Taiping and Donghak popular movements were not only comparable in the time and the context in which the movements happened, but they also were compared in their ideologies and the consequences to the dynasties. The Qing and the Joseon were the last dynasties of China and Korea to be faced similarly with both internal disturbances and the external influences of imperialism from the beginning of the nineteenth century. The Taiping popular movement (1851-1864) occurred in the late Qing (1644-1912) dynasty and was incubated in the impoverished southernmost area, full of radical ethnic discrimination. Likewise, the Donghak popular movement (1894-1895) emerged in the late Joseon (1392-1910) dynasty in the Southern provinces where many suffered from poverty and corruption from local officers. Their ideologies for the movements were based on religious dogma, egalitarianism, and being anti-foreigner. The Taiping principles were the combination of Christianity and ancient Chinese beliefs, the utopian ideal of equality in the land and treasury, anti-Manchus, and anti-Confucianism. Comparably, the Donghak concepts were humanism, farmland distribution, and “Donghak Religion” - Eastern Learning, founded in the 1860s by Choe Je-u. The Donghak religion, which was recently known as Cheondoism or The Heavenly Way, was a fusion idea of Confucianism, Taoism, Buddhism, and Korean Shamanism. It was used to react to the “Seohak” - Western Learning.